1998
DOI: 10.1021/cm970351l
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for an Ion-by-Ion Deposition Mechanism in Solution Growth of CdS Thin Films

Abstract: A systematic investigation of the mechanism of cadmium sulfide solution growth using atomic force and scanning electron microscopy was performed. The process that was studied involved the slow generation of sulfide ions via the controlled hydrolysis of thiourea in the presence of cadmium nitrate and triethanolamine, a chelating ligand. The formation of two types of films was observed, a mirrorlike primary film and a secondary layer of larger particles that was loosely attached to the first film. The substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Factors influencing the formation of CSCS: Thiourea (TU), a sulfur source which has been commonly used for the deposition of metal-sulfide films [28,29] or other nanostructures in basic solutions, [30][31][32] remains stable up to 180 8C in reaction systems without metal cations. However, this compound decomposes at relatively low temperatures in an aqueous solution in the presence of many metal cations including Cd 2 + .…”
Section: Resultsmentioning
confidence: 99%
“…Factors influencing the formation of CSCS: Thiourea (TU), a sulfur source which has been commonly used for the deposition of metal-sulfide films [28,29] or other nanostructures in basic solutions, [30][31][32] remains stable up to 180 8C in reaction systems without metal cations. However, this compound decomposes at relatively low temperatures in an aqueous solution in the presence of many metal cations including Cd 2 + .…”
Section: Resultsmentioning
confidence: 99%
“…The growth mechanism of CdS films by Chemical bath deposition (CBD) has been discussed by different authors [14][15][16][17][18][19][20][21][22][23][24][25]. It is reported that the reaction rate often takes an important role on the morphology conversion in sulfide deposition.…”
Section: Some Relevant Information Of Cds Depositionmentioning
confidence: 99%
“…Cadmium sulfide (CdS) is a wide band gap semiconductor, which has been widely investigated as photoelectrical materials and nanostructured materials [10][11][12][13][14][15][16][17][18][19][20]. Many researches have been reported on the fabrication of CdS thin films on solid substrates by sputtering [10], thermal evaporation [11], self-assembly growth [12], epitaxial electrodeposition [13], etc.…”
Section: Introductionmentioning
confidence: 99%
“…These deviations result from dimensionality of nanometer sized grains and numerous interfaces between adjacent crystallites (Tong and Zhu 2006). A major research goal of recent years is to understand the size dependent properties of nanocrystalline materials and as a result considerable amount of work on synthesis and characterization of nanocrystalline thin films are being carried out (Nandakumar et al 1997;Breen et al 1998;Behera et al 2000;He et al 2003).…”
Section: Introductionmentioning
confidence: 99%